2003
DOI: 10.1093/bja/aeg195
|View full text |Cite
|
Sign up to set email alerts
|

Propacetamol augments inhibition of platelet function by diclofenac in volunteers

Abstract: The combination of propacetamol and diclofenac inhibits platelet function more than diclofenac alone. This should be considered when assessing the risk of surgical bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
27
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 25 publications
0
27
1
Order By: Relevance
“…Yet, in vivo studies have failed to prove competitive interaction between aspirin and diclofenac in platelet aggregation, or suggest minimal effect of diclofenac on platelet aggregation, when administered concurrently with aspirin [9,10] . On the other hand, additive or synergistic effects between antiplatelet agents acting via different mechanisms as well as paracetamol, a weak COX inhibitor and diclofenac have been demonstrated [11][12][13] . But how could synergistic or even additive effect between aspirin that irreversibly blocks COX I activity and diclofenac that reversibly blocks COX I activity be justified?…”
Section: Discussionmentioning
confidence: 99%
“…Yet, in vivo studies have failed to prove competitive interaction between aspirin and diclofenac in platelet aggregation, or suggest minimal effect of diclofenac on platelet aggregation, when administered concurrently with aspirin [9,10] . On the other hand, additive or synergistic effects between antiplatelet agents acting via different mechanisms as well as paracetamol, a weak COX inhibitor and diclofenac have been demonstrated [11][12][13] . But how could synergistic or even additive effect between aspirin that irreversibly blocks COX I activity and diclofenac that reversibly blocks COX I activity be justified?…”
Section: Discussionmentioning
confidence: 99%
“…However, recent studies of human volunteers have shown greater inhibition of thromboxane A2 release with a combination of diclofenac and paracetamol compared to diclofenac, suggesting that the combination may be associated with more side effects. 18 Furthermore, an animal model has shown that the combination of diclofenac and morphine is synergistic and the combination of paracetamol and morphine is additive. 19 However, since this study was completed, we have changed our choice of spinal opioid from fentanyl to diamorphine, and dispensed with PCA morphine.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Hegi et al [12] compared the effect of selective COX-2 blocker rofecoxib and nonselective COX inhibitor diclofenac in patients undergoing gynaecological and breast surgery, and found increased estimated blood loss and greater reduction in haemoglobin in nonselective COX inhibitor users, and Graff et al [13] showed that there is an association between COX inhibition and haemorrhagic complications in various clinical settings. In a recent systematic review of NSAIDs and bleeding after tonsillectomy, increased risk for reoperation after use of NSAIDs was found [14,15]. Likewise pretreatment with ibuprofen appears to increase perioperative blood loss during hip replacement [16] and low-dose aspirin has the same effect given before transurethral Bleeding Severity Score of Patients With Normal and Impaired Platelet Function prostatectomy [17].…”
Section: Discussionmentioning
confidence: 99%